PENGARUH KESEHATAN BPR TERHADAP PENYALURAN KREDIT MELALUI STRATEGI PEMBERIAN KREDIT SEBAGAI PEMEDIASI - Gede Agus Dian Maha Yoga; Ni Kadek Suryani (Widya Manajemen, 2018)
This study aims to 1) analyze the influence of rural banks health on lending strategies, 2) analyze the influence of rural banks health on lending, 3) analyze the effect of lending strategies on lending, 4) analyze the influence of rural banks health on lending through lending strategies as mediator. The study was conducted in Bali province, using a combination of primary and secondary data. Using the technique of population samples or saturated samples. Partial Least Square (PLS) is a data analysis technique used. The results of the analysis show that 1) the health of rural banks to the strategy of lending has a significant positive effect, 2) the health of rural banks to lending has a significant positive effect, 3) the strategy of lending to lending has a significant positive effect, 4) the health of rural banks indirectly affects lending through lending strategies as a significant mediator for rural banks in Bali province.